(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the hygienic assessment of dietary nutrition in patients who underwent colostomy surgery from a clinical and preventive medicine perspective. Nutritional management after colostomy is a decisive factor influencing intestinal adaptation, wound healing, metabolic stability, stool regulation, and the patient’s overall quality of life. In the early and late postoperative periods, patients often face a number of diet-related challenges, including irregular bowel output, excessive gas formation, odor, dehydration, electrolyte imbalance, reduced appetite, and poor tolerance to certain foods. These conditions require a scientifically grounded dietary regimen based on hygienic principles, physiological needs, and the functional state of the gastrointestinal tract. The study emphasizes that dietary support for colostomy patients should not be limited to caloric adequacy alone, but must also include meal timing, food consistency, nutrient balance, sanitary quality, fluid intake, and individual tolerance. Special attention is paid to the gradual expansion of the diet, the role of protein-rich and vitamin-containing foods in tissue recovery, and the hygienic prevention of gastrointestinal irritation and infectious complications. The article also highlights the importance of patient education regarding safe food selection, meal preparation, and self-monitoring of intestinal response. It is concluded that a hygienically optimized dietary approach contributes significantly to postoperative recovery, complication prevention, digestive comfort, and long-term rehabilitation in patients after colostomy surgery.